A survey on Iranian midwives’ knowledge about COVID-19 during pregnancy, delivery, postpartum, and neonatal feeding - Fatemeh Azarkish; Roksana Janghorban (Journal of Infection in Developing Countries)
Introduction: The COVID-19 pandemic has impacted the care that maternal and newborn health professionals, especially midwives, provide. If they know how to care for COVID-19 patients during pregnancy, delivery, and postpartum, they can manage these cases better. The study aimed to identify the knowledge of Iranian midwives about COVID-19 during pregnancy, delivery, postpartum, and neonatal feeding.